2018
DOI: 10.3390/nu10070889
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of High-Intensity Interval and Moderate-Intensity Continuous Exercise on GLP-1, Appetite and Energy Intake in Obese Men: A Crossover Trial

Abstract: This study investigated the effect of high-intensity interval (HIIE) and moderate-intensity continuous exercise (MICE) on glucagon-like peptide 1 (GLP-1), appetite and energy intake (EI) in obese men. In a randomized crossover trial, 12 participants (28.4 ± 2.6 years, 35.5 ± 4.5 kg/m2, 39.8 ± 2.2% body fat) performed: (I) Control (CON, no exercise); (II) MICE (20 min, 70% of maximal heart rate) and (III) HIIE (10 × 1 min at 90% of maximal heart rate with 1 min recovery). GLP-1 and appetite were assessed at: (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
2
26
0
1
Order By: Relevance
“…Likewise, in another study [ 34 ] of the effects of MICT (50-min at 70% VO 2max ) and HIIT (6 × 3-min at 90% VO 2max with 3-min active recovery) in combination with short exposure to hypoxia on appetite in 12 healthy male participants, the appetite responses did not appear to be influenced by the exercise modality. A more recent study [ 35 ] of 12 obese men also suggested that neither HIIT (10 × 1-min at 90% HR max with 1-min recovery) nor MICT (20-min at 70% HR max ) altered the energy intake at 1 or 24 h post-exercise, despite an apparent transient reduction in hunger immediately following HIIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in another study [ 34 ] of the effects of MICT (50-min at 70% VO 2max ) and HIIT (6 × 3-min at 90% VO 2max with 3-min active recovery) in combination with short exposure to hypoxia on appetite in 12 healthy male participants, the appetite responses did not appear to be influenced by the exercise modality. A more recent study [ 35 ] of 12 obese men also suggested that neither HIIT (10 × 1-min at 90% HR max with 1-min recovery) nor MICT (20-min at 70% HR max ) altered the energy intake at 1 or 24 h post-exercise, despite an apparent transient reduction in hunger immediately following HIIT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individual variability in food intake responses should not be overlooked, as the present data revealed a relatively large variance in total energy intake. Moreover, the potential effects of obesity level and sex on the appetite response to HIIT remains under debate [ 35 , 40 ]. Accordingly, future studies comparing normal-weight and obese individuals of different sexes are also warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a potential role of blood lactate should be considered given that it binds to ghrelin-producing cells during exercise and inhibits their secretory function (18,35). Finally, a previous study using similar exercise protocols in obese men found a transient suppression on hunger perception after HIIE, but not after MICE, which may contribute to a reduced post-exercise energy intake (30).…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, obesity is considered as a worldwide problem, and is defined as abnormal or excessive fat accumulation that impairs health [1]. However, recent reports indicate that obesity rates have doubled worldwide in recent years and women are more likely to be obese or overweight than men [2].…”
Section: Introductionmentioning
confidence: 99%
“…Design and exercise protocol At first, the subjects were evaluated in the form of the control group and then examined with an interval of 10 days in the experimental group form. In the experimental session, the subjects performed 10 exercises, 1 minute running on treadmill at 90% HRmax and with 1 minute rest interval between exercises at 30% HRmax [1]. It should be noted that subjects did not perform any exercises in the control session and only blood samples were taken from them and the visual analog scale (VAS) was completed by them; energy intake was also reported.…”
Section: Introductionmentioning
confidence: 99%